Nivolumab-associated digital small-vessel vasculitis in a patient with an advanced renal cell carcinoma. (21st February 2019) - Franco, Fernando; Méndez, Miriam; Gutierrez, Lourdes; Sanz, Jesús; Calvo, Virginia; Provencio, Mariano
The immunotherapy (IO) agents in the renal cell carcinoma represent the best option in the second line of treatment. However, these drugs can be associated with different types of toxicities. The vascular toxicity related with IO is very uncommon. We report a case of a 46-year-old man diagnosed with stage IV renal cell carcinoma. He received a second-line treatment with nivolumab. After the fourth cycle, he presented a small-vessel serious vasculitis associated with IO toxicity. He required treatment with corticosteroids and immunosuppressors for toxicity control. We speculate that the anti-PD-1 agents can generate a disproportionate vascular inflammatory process mediated by T cells. The data suggest that there is an intimate relationship between alterations in the PD-1/PD-L1 pathway and vasculitis.